2014
DOI: 10.3892/ijo.2014.2264
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of autophagic genes sensitizes CUG2-overexpressing A549 human lung cancer cells to oncolytic vesicular stomatitis virus-induced apoptosis

Abstract: Abstract. We showed in our previous study that cancer upregulated gene (CUG) 2, a novel oncogene, confers resistance to infection of oncolytic vesicular stomatitis virus (VSV) by activating Stat1-mediated signal transduction. Since many studies have reported that autophagy is involved in virus replication, we investigated whether autophagy also plays a role in the antiviral activity in A549 cells overexpressing CUG2 (A549-CUG2). We suppressed Atg5 or Beclin 1 expression using siRNA and examined its effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Our results revealed that endogenous Smac was diminished when HeLa cells were infected by wtVSV for 24 hr. The exact mechanisms of inhibition remain to be determined, but VSV has been shown to activate autophagy and ubiquitination to inhibit apoptosis 41, 42, 43. On the other hand, the level of Smac in HeLa cells was maintained or enhanced throughout the 24-hr course of VSV-S infection (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that endogenous Smac was diminished when HeLa cells were infected by wtVSV for 24 hr. The exact mechanisms of inhibition remain to be determined, but VSV has been shown to activate autophagy and ubiquitination to inhibit apoptosis 41, 42, 43. On the other hand, the level of Smac in HeLa cells was maintained or enhanced throughout the 24-hr course of VSV-S infection (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, suppressing autophagy genes (Atg5 or Beclin-1) by siRNA increased reactive oxygen species formation and decreased ISG15 expression, which sensitized CUG2-overexpressing A549 human lung cancer cells to VSV-induced apoptosis. Chemical agents targeting autophagy genes such as Atg5 and Beclin-1 would be promising for CUG2-overexpressing cancers [93]. Another novel target is Livin, which is a member of the inhibitors of the apoptosis family.…”
Section: Increasing Direct Oncotoxicitymentioning
confidence: 99%
“…Centromeric protein W (CENPW), also known as cancer upregulated gene 2 (CUG2) protein, is overexpressed in multiple tumor tissues, including cervical, colon, liver, and lung cancers (Malilas et al, 2014). The CENPW is located at human chromosome 6q22.32 and is regulated by the upstream TSS region, which can transcribe a full-length mRNA of 600 bp (Lee et al, 2007).…”
Section: Introductionmentioning
confidence: 99%